2009
DOI: 10.1111/j.1365-294x.2009.04111.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of environment and life‐history traits on the distribution of genes and individuals: a comparative study of 11 rainforest trees

Abstract: This study investigates patterns of genetic connectivity among 11 co-distributed tropical rainforest tree species from the genus Elaeocarpus across a biogeographic barrier, the Black Mountain Corridor (BMC) in the Australian Wet Tropics (AWT). We analysed a combination of allelic and flanking region sequence data from microsatellite markers, and evaluated the relative influence of environmental preferences and functional traits on genetic diversity and gene flow. The results indicate that only in three species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 69 publications
(80 reference statements)
0
45
0
Order By: Relevance
“…However, it is worth noting that degrees of genetic isolation between rainforest trees across fragments of the Australian Wet Tropics have been linked to fruit size and dispersal mode in otherwise ecologically similar species [91,92]. This is an important observation and highlights that climate-based ecological modeling alone cannot fully explain species’ current distributions, nor adequately predict past ranges or barriers to gene-flow [93].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that degrees of genetic isolation between rainforest trees across fragments of the Australian Wet Tropics have been linked to fruit size and dispersal mode in otherwise ecologically similar species [91,92]. This is an important observation and highlights that climate-based ecological modeling alone cannot fully explain species’ current distributions, nor adequately predict past ranges or barriers to gene-flow [93].…”
Section: Discussionmentioning
confidence: 99%
“…The influence of environmental and ecological factors, and functional traits (including those related to dispersal), on the assemblage of Australian rainforest plant species at plot, local area, regional, and continental scales has been tested using genetic, phylogenetic, and plot-based ecological and functional trait methods [21][25]. In addition, how those factors impacted on evolutionary history and local assemblage processes [21], and how the processes differed across regions at continental scales [26], [27] has been investigated for some species and clades. In several cases, research results have suggested more of a continuum of genetic diversity and distributions across broad geographic extents [23], [28].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic differentiation drives genetic diversity (Schaal et al, 1991) and the relationship between genetic differentiation and environmental factors has been a focus of recent studies (Rossetto et al, 2009;Finger et al, 2010;Santos et al, 2010;Martins et al, 2011). Random amplified polymorphic DNA (RAPD) markers can cover the total genome of organisms, including coding and noncoding regions, and reflect differences in the whole genome (Garcia et al, 1998).…”
Section: Introductionmentioning
confidence: 99%